Thermal treatment of carbon-fibre-reinforced polymers (Part 2: Energy recovery and feedstock recycling). Issue 6 (June 2022) - Stockschläder, Jan; Quicker, Peter; Baumann, Werner; Wexler, Manuela; Stapf, Dieter; Beckmann, Michael; Thiel, Christopher; Hoppe, Helmut
The use of carbon fibre (CF)-reinforced plastics has grown significantly in recent years, and new areas of application have been and are being developed. As a result, the amount of non-recyclable waste containing CF is also rising. There are currently no treatment methods for this type of waste. Within this project different approaches for the treatment of waste containing CF were investigated. Main subject of the research project were large-scale investigations on treatment possibilities and limits of waste containing CF in high temperature processes, with focus on the investigation of process-specific residues and possible fibre emission. The results showed that the two conventional thermal waste treatment concepts with grate and rotary kiln firing systems are not suitable for a complete oxidation of CFs due to the insufficient process conditions (temperature and dwell time). The CFs were mainly discharged via the bottom ash/slag. Due to the partial decomposition during thermal treatment, World Health Organization (WHO) fibres occurred in low concentrations. The tests run in the cement kiln plant have shown the necessity of comminution for waste containing CF. With respect to the short testing times and moderate quantities of inserted CF, a final evaluation of the suitability of this disposal path was not possible. The use of specially processed waste containing CF (carbon-fibre-reinforced plastic (CFRP) pellets) as a carbon substitute in calcium carbide production led to high carbon conversion rates. In the unburned furnace dust, which is marketed as a by-product of the process, CFs in relevant quantities could be detected.